PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA PERUM BULOG KANWIL SUMUT - Karnila Manurung (JOURNAL ECONOMICS AND STRATEGY, 2021)
Training is essential to improve skills; the more skilled employees are in their fields, the better their work results. Also, discipline must be enforced for the smooth running of a job. In this study the entire population was sampled, amounting to 42 employees. The analysis technique used is multiple linier regression analysis. The result showed that the training and work discipline variables partially and simultaneously have a positive and significant effect on performance variables.